Learning a Large Scale of Ontology from Japanese Wikipedia - Tamagawa, Susumu; Sakurai, Shinya; Tejima, Takuya; Morita, Takeshi; Izumi, Noriaki; Yamaguchi, Takahira (2010 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology, 2010)
Here is discussed how to learn a large scale of ontology from Japanese Wikipedia. The learned ontology includes the following properties: rdfs:subClassOf (IS-A relationships), rdf:type (class-instance relationships), owl:Object/DatatypeProperty (Infobox triples), rdfs:domain (property domains), and skos:altLabel (synonyms). Experimental case studies show us that the learned Japanese Wikipedia Ontology goes better than already existing general linguistic ontologies, such as EDR and Japanese WordNet, from the points of building costs and structure information richness.